Acetylation of Emodin and Cytotoxic Activity Effect Against HepG2 Cell Lines - Firdayani, Firdayani; Nuralih, Nuralih; Kusumastuti, Siska Andrina; Hasan, Hasan (Proceedings of International Pharmacy Ulul Albab Conference and Seminar (PLANAR); Vol 2 (2022): Proceedings of International Pharmacy Ulul Albab Conference and Seminar (PLANAR), 2022)
Emodin (1,3,8-trihydroxy-6-methyl-9,10-anthraquinone) is an anthraquinone bioactive compound used as a lead compound because it exhibits potential anticancer properties. Structural modifications were made at the C3 position and its relationship to cytotoxic activity against the HepG2 cell line to determine the pharmacophore group of this compound. The hydroxy group at C3 emodin is converted to an ester group to produce 3-acetyl emodin. In addition, docking simulations into the cancer target protein casein kinase-2 were also carried out to predict molecular interactions. Emodin was reacted with anhydrous acetate and confirmed the product confirmation using LCMS/MS, FTIR, 1 H-NMR, and 13 C-NMR. Emodin and 3-acetyl emodin were tested for cytotoxicity against HepG2 cells in vitro . Cytotoxic emodin and 3-acetyl emodin tests on HepG2 cells resulted in Cytotoxic concentrations 50 (CC 50 ) of 0.54 mM and 0.42 mM, respectively. The results showed that modifying the C3 hydroxyl group with acetyl can increase the cytotoxic effect more than emodin. This research is expected to provide information regarding the structure-activity relationship of emodin in cancer cells and the expansion of new drug applications for additional cancers.